2016
DOI: 10.1186/s12891-016-1075-y
|View full text |Cite
|
Sign up to set email alerts
|

Pain management among Dominican patients with advanced osteoarthritis: a qualitative study

Abstract: BackgroundAdvanced osteoarthritis and total joint replacement (TJR) recovery are painful experiences and often prompt opioid use in developed countries. Physicians participating in the philanthropic medical mission Operation Walk Boston (OpWalk) to the Dominican Republic have observed that Dominican patients require substantially less opioid medication following TJR than US patients. We conducted a qualitative study to investigate approaches to pain management and expectations for postoperative recovery in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…They reported a reliance on nonpharmacologic therapies, as well as family and religious support. They had limited knowledge of opioids, and trusted God and their doctors to cure their pain 28 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported a reliance on nonpharmacologic therapies, as well as family and religious support. They had limited knowledge of opioids, and trusted God and their doctors to cure their pain 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, Op-Walk Boston’s use of qualitative studies allowed for an increased understanding of the differences in medical practices, catalyzed adaptation to cultural norms, and identified needed interventions. For example, studies on patient opioid use and physician opinions on prescription medications showed that HGPS physicians rarely prescribed opioids, and patients had limited experience with them 27,28 . These observations prompted the Op-Walk clinical leaders to reduce the role of opioids in the postoperative pain management protocols for the program, as well as to evaluate the reasoning for their prescription practices at their home institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous qualitative studies in the same setting (Hospital General de la Plaza de la Salud, Santo Domingo) investigated modes of coping with arthritis. Yu and colleagues found that participants coped with pain while utilizing relatively little pain medication, in part by using nonpharmacologic therapies and social support networks . Niu et al similarly identified strategies that patients used to manage pain without medication (e.g., prayer) and to obtain medication (e.g., family financial support) .…”
Section: Discussionmentioning
confidence: 99%
“…In the latter category, religion often plays an important role in dealing with illness . Purchasing treatments places a sizeable financial burden on individuals in low‐ and middle‐income countries , leaving them to forego part of the treatment or identify additional resources . Higher out‐of‐pocket costs contribute to lower adherence , and individuals with lower socioeconomic status are less likely to adhere to treatment regimens .
In a middle‐income country with stark income inequality (Dominican Republic), there is societal decision‐making that perpetuates a lack of access to health care. When available resources are insufficient for accessing health care, there is a range of strategies used by Dominican individuals to manage chronic illness. Knowledge regarding strategies that patients may use to manage chronic illness when lacking resources for medications is beneficial for clinicians working in resource‐limited settings. There is a need for policies that address underinsurance and transportation‐related barriers to care.
…”
Section: Introductionmentioning
confidence: 99%
“…Although some qualitative studies have examined the experiences of patients of the management of chronic pain [15][16][17][18] as well as OA pain, they have examined pharmacotherapy for pain management in developed countries [19] or have examined the patients' experiences after surgical interventions [20]. No comprehensive studies have yet investigated the expectations of patients with OA of pharmacological pain management strategies and the challenges faced in developing countries in accordance with their local culture, beliefs and attitudes.…”
Section: Introductionmentioning
confidence: 99%